PELATIHAN STRATEGI PENINGKATAN PENJUALAN PRODUK DAN PEMBUATAN LAPORAN KEUANGAN SEDERHANA PADA BEFO - Efi Fitriani; Dani Ramdani; Bimbim Maghriby (Jurnal Publika Pengabdian Masyarakat, 2019)
The community service program aims to provide training on methods for increasing product sales, making halal certification from MUI and making simple financial financial statements on Befo. The specific target to be achieved is to be able to increase sales of Befo products, and make financial reports simply. The method used is to provide training in a strategy method for increasing product sales and training in terms of simple financial reporting. With the training that will be provided by the implementation team, the Befo business is expected to be more developed with the increase in product sales and simple financial reports. The results of this service are the implementation of training strategies to increase sales of simple financial reporting products on Befo. Then the other results achieved were an increase in business circulation in product sales and a simple financial report on Befo.Keywords: Training Methods for Increasing Product Sales Strategies, Training on Making Financial Statements Simply